Impairments of hepatic gluconeogenesis and ketogenesis in PPARα-deficient neonatal mice - Cotter, David G. (American Physiological Society, 2014)
Peroxisome proliferator activated receptor-α (PPARα) is a master transcriptional regulator of hepatic metabolism and mediates the adaptive response to fasting. Here, we demonstrate the roles for PPARα in hepatic metabolic adaptations to birth. Like fasting, nutrient supply is abruptly altered at birth when a transplacental source of carbohydrates is replaced by a high-fat, low-carbohydrate milk diet. PPARα-knockout (KO) neonatal mice exhibit relative hypoglycemia due to impaired conversion of glycerol to glucose. Although hepatic expression of fatty acyl-CoA dehydrogenases is imparied in PPARα neonates, these animals exhibit normal blood acylcarnitine profiles. Furthermore, quantitative metabolic fate mapping of the medium-chain fatty acid [(13)C]octanoate in neonatal mouse livers revealed normal contribution of this fatty acid to the hepatic TCA cycle. Interestingly, octanoate-derived carbon labeled glucose uniquely in livers of PPARα-KO neonates. Relative hypoketonemia in newborn PPARα-KO animals could be mechanistically linked to a 50% decrease in de novo hepatic ketogenesis from labeled octanoate. Decreased ketogenesis was associated with diminished mRNA and protein abundance of the fate-committing ketogenic enzyme mitochondrial 3-hydroxymethylglutaryl-CoA synthase (HMGCS2) and decreased protein abundance of the ketogenic enzyme β-hydroxybutyrate dehydrogenase 1 (BDH1). Finally, hepatic triglyceride and free fatty acid concentrations were increased 6.9- and 2.7-fold, respectively, in suckling PPARα-KO neonates. Together, these findings indicate a primary defect of gluconeogenesis from glycerol and an important role for PPARα-dependent ketogenesis in the disposal of hepatic fatty acids during the neonatal period.